Gambaran Status Gizi dan Frekuensi Diare pada Balita Usia 0 Sampai 59 Bulan di Puskesmas Donggala Kabupaten Donggala: Description Of Nutrition And Frequency Of Diarrhea Status In Toddlers Age 0 To 59 Months In Donggala Clinics, Donggala District - Elvyrah Faisal; Putu Candriasih; Ni Putu Ani pratiwi (Svasta Harena: Jurnal Ilmiah Gizi, 2020)
Nutritional status is an expression of the state of the body that is affected by consumption of food and nutrients. Nutritional status in infants is influenced by both direct and indirect factors. The immediate factor is food intake and disease. This study aims to determine the nutritional status and frequency of diarrhea in toddlers aged 0 to 59 months at the Donggala Health Center in Donggala Regency. This research is a descriptive study that is a study conducted to see a picture of nutritional status in children aged 0 to 59 months at the Donggala Health Center in Donggala Regency. The study population was 78 toddlers suffering from symptoms based diarrhea. The data obtained are secondary data from the Donggala Health Center. The results of this study indicate that toddlers who experience malnutrition and malnutrition as much as 35.9%, over 7.7% nutrition from 78 toddlers. Based on PB / U, toddlers are very short and 35.9% short, toddlers are 7.7% tall. Whereas based on BB / PB, toddlers are very thin and thin 15.4% and there are no toddlers with fat nutritional status. Frequency of diarrhea based on criteria of diarrhea with severe dehydration 16.7%, mild dehydration diarrhea 38.5%, diarrhea without dehydration 37.2% and dysentery 7.7%. The conclusion of this study is that the nutritional status of children under five who suffer from diarrhea based on the indicators BB / U and PB / U mostly 56.4% normal nutritional status. While the results of the BB / PB indicators are mostly toddlers with normal nutritional status (84.6%). The highest frequency of diarrhea based on the criteria of diarrhea with mild to moderate dehydration is 30 people (38.5%).